Evaluating Impacts of Public Transit and Automobiles During Connected and Automated Vehicle Adoption - Xinmeizi Cai; Hang Zhou; Chengyuan Ma; Xiaopeng Li; Bin Ran (Journal of Advanced Transportation)
The adoption of connected and automated vehicles (CAVs) and automated vehicles (AVs) is expected to improve overall travel efficiency in traffic networks. However, this improvement may vary across multimodal road traffic, influencing the equity of travel experiences among different income groups. This study evaluates the equity effects of AV deployment during its gradual adoption in public transit and automobiles. Five scenarios with varying penetration rates are designed to represent the transition from HVs to CAVs in public transit and automobiles. Different model parameters were calibrated to represent HVs, AVs, and CAVs, and four measurements of effectiveness were developed to compare travel experiences between high-income individuals, who primarily rely on private automobiles, and low-income individuals, who depend on public transit. A detailed case study was conducted using real-world road network and traffic flow data from Madison, Wisconsin. Simulation results reveal that while AV adoption improves overall traffic efficiency, including nonupgraded vehicles, it also exacerbates disparities in travel performance between high- and low-income groups, even with efforts to expand AV-enabled public transit.